The Role of Banking Financial Technology in Reducing GHG Emissions: A Study of ASEAN Banks - Herlina Herlina; Matius Surya Mulyana (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Technological advancements facilitate the mitigation of Greenhouse gas (GHG) emissions. Technological advancements in the economic sector yield diverse breakthroughs and enhance managerial efficacy, fostering favourable economic expansion. The banking business is a key economic sector that has the potential to promote and encourage ESG. The banking business is committed to enhancing ESG as banks own financial instruments that support ESG and permeate all facets of their business. Sustainable financial technology reduces greenhouse gases by supporting ESG. The research question formulated in this study is whether the implementation of sustainable financial technology in ASEAN countries has an impact on GHG emissions. The research sample included 25 banks in ASEAN. The research utilises secondary data as sustainable financial report documents from 2019 to 2021. A total of 75 panels were included in this study. Using sustainable financial technology benefits GHG emissions, with a statistical significance of 1%. The impact of implementing sustainable financial technology on GHG emissions is 24.7845%.